Transcriptional control of human papillomavirus (HPV) oncogene expression: composition of the HPV type 18 upstream regulatory region. - Butz, K (1993)
The malignant transformation potential of high-risk human papillomaviruses (HPVs) is closely linked to the expression of the viral E6 and E7 genes. To elucidate the molecular mechanisms resulting in HPV oncogene expression, a systematic analysis of the cis-regulatory elements within the HPV type 18 (HPV18) upstream regulatory region (URR) which regulate the activity of the E6/E7 promoter was performed. As the functional behavior of a given cis-regulatory element can be strongly influenced by the overall composition of a transcriptional control region, individual elements were inactivated by site-directed mutagenesis in the physiological context of the complete HPV18 URR. Subsequently, the effects of these mutations on the activity of the E6/E7 promoter were assessed by transient transfection assays. We found that the transcriptional stimulation of the E6/E7 promoter largely depends on the integrity of cis-regulatory elements bound by AP1, SP1, and in certain epithelial cells, KRF-1. In contrast to previous reports by implying a key role for NF1 and Oct-1 recognition motifs in the stimulation of papillomavirus oncogene expression, the inactivation of these elements in the context of the HPV18 URR did not strongly affect the transcriptional activity of the E6/E7 promoter. Mutation of a promoter-proximal glucocorticoid response element completely abolished dexamethasone inducibility of the HPV18 E6/E7 promoter and resulted in an increase of its basal activity. Functional dissection of the HPV18 constitutive enhancer region indicates that its transcriptional activity is largely generated by functional synergism between a centrally located AP1 module and thus far undetected cis-active elements present in the 5' flank of the enhancer. Furthermore, comparative analyses using homologous and heterologous promoters show that the transcriptional activity of HPV18 enhancer elements is influenced by the nature of the test promoter in a cell-type-specific manner.